Phototherapy Implementation for Neonatal Jaundice: A Case Study - Yolanda, Henny; Thoyibah, Zurriyatun; Andriani, Baiq Nia (Universitas Tanjungpura, 2025)
Background: Hyperbilirubinemia is a major cause of neonatal jaundice and can result in serious neurological complications if not managed appropriately. Phototherapy is one of the effective interventions for reducing bilirubin levels in newborns. Objective: To evaluate the clinical effectiveness of phototherapy implementation in reducing bilirubin levels and jaundice severity in newborns with neonatal jaundice in the NICU setting. Methods: This was a descriptive case study of two infants with neonatal jaundice in the NICU ward of Siti Hajar Islamic Hospital Mataram in November 2023. Data were collected through direct observation, clinical documentation, and physical examination using standard guidelines for jaundice degrees according to Kramer. Results: After phototherapy for 3 days, there was a decrease in bilirubin levels in both patients. Patient 1 showed a reduction in jaundice degree from level V to III, and patient 2 from level IV to II, with an average decrease in bilirubin levels of 3.7 mg/dL. Conclusion: Phototherapy proved effective in reducing bilirubin levels in infants with neonatal jaundice. This intervention can be optimally implemented in NICU units as part of evidence-based neonatal nursing care.